The Shawshank redemption [videorecording (DVD)] - Darabont, Frank; Robbins, Tim, 1958-; Freeman, Morgan; Gunton, Bob; King, Stephen, 1947-; King, Stephen, 1947- (Warner Home Video, 2007)
Two convicts, one white and one black, never give up the dream of freedom, and together they turn hope and friendship into an uplifting bond no prison can ever take away.